Submission to the United Nations Committee on the Elimination of Racial Discrimination : Parallel Report on the 21st to 23rd Periodic reports of the United Kingdom under the International Convention on the Elimination of All forms of Racial Discrimination.: Parallel Report on the 21st to 23rd Periodic reports of the United Kingdom under the International Convention on the Elimination of All forms of Racial Discrimination. (2016) - Northern Ireland., Human Rights Commission,
No abstract available